Cost-volume-profit analysis and the value of information: an evaluation for the normal and lognormal distributions - Richardson, A. William; McMaster University, Faculty of Business (My University, 1987)
In contrast to most papers dealing with cost-volume-profit analysis which focus on the decision to accept or reject a project, this paper examines the decision whether or not to seek improved information about the inputs to the decision model. The maximum benefit from this information seeking process is measured by the expected value of perfect information. Expressions for the expected value of perfect information for the lognormal distribution, an. asymmetric distribution which is generally more realistic in such decisions, are presented. The results from these expressions are compared to those obtained from the expression for the normal distribution over a range of parameters. This comparison shows that the results for the normal distribution approximate those for the lognormal distribution only over a narrow range of parameters.
20 p. ; Includes bibliographical references (p. 15-16). ; "February, 1987." ; The financial support of the Accounting Research and Education Centre of the Faculty of Business, McMaster University, is gratefully acknowledged.